A multiple criteria sorting method for supporting the maintenance management of medical ventilators: The case of Hospital da Luz Lisboa. (April 2023) - Pinho, Margarida; Costa, Ana Sara; Meneses, Marta; Manso, Joana
Abstract: Medical equipment is characterized by a constant flow of innovations, which is transforming the delivery of healthcare. This creates the need for healthcare organizations to incorporate methodologies to support the maintenance management of these equipment. Within this context, Luz Saúde, the holding company of one of the largest healthcare groups in Portugal, intends to complement the medical equipment maintenance management program of the biggest hospital in its network, Hospital da Luz Lisboa . To this aim, we develop a decision aiding tool for assessing the maintenance condition of medical ventilators and recommend a plan of action. For that, we apply a multicriteria decision aiding methodology, utilizing the Electre Tri-nC method. In interaction with the decision makers, we construct a model using twelve criteria for assigning ventilators to one of the five ordered categories representing the current condition (excellent, very good, good, adequate, and poor). Most of the medical ventilators in the analysis were considered in adequate or good maintenance conditions, which was consistent with the decision makers' expectations. A detailed analysis of the results evidenced the robustness of the model. This study constitutes the first step toward the use of multicriteria methodologies for supporting decision processes in Hospital da Luz Lisboa . Highlights: Medical ventilators maintenance condition assessment needs a decision support tool. Application of a multiple criteria decision aiding approach. Construction of a model for assessing the overall condition of medical ventilators. Relevant implications for supporting the maintenance management of medical equipment.